Preliminary inventory of scale insects on mango trees in Benin - Germain, J.-F.; Vayssieres, J.-F.; Matile-Ferrero, D. (ENTOMOLOGIA HELLENICA, 2010)
A preliminary inventory of scale insects (Hemiptera: Coccoidea) developing on the mango tree is presented for Northern and Central Benin. The following species, Gigantococcus euphorbiae, Gigantococcus nigroareolatus, Ceroplastes uapacae, Parasaissetia nigra, Saissetia privigna, Udinia catori, Ferrisia virgata, Paracoccus interceptus, Phenacoccus solenopsis, Rastrococcus invadens, Aonidiella orientalis and Lepidosaphes tapleyi, were collected from 2005 to 2007 in mango orchards in the Sudanian area of Benin, on branches, leaves, and particularly on mango petioles and fruits. Nine of these species are recorded for the first time in Benin while P. interceptus is recorded in Africa for the first time. Only two, R. invadens and A. orientalis, of the 12 species are considered as mango pests.